2000
DOI: 10.1136/gut.46.4.474
|View full text |Cite
|
Sign up to set email alerts
|

The 5-HT3 receptor antagonist alosetron inhibits the colorectal distention induced depressor response and spinal c-fos expression in the anaesthetised rat

Abstract: Background-Noxious intestinal distention elicits a reflex depressor response in the sodium pentobarbitone anaesthetised rat, which can be used as an index of visceral nociception. 5-HT 3 receptor antagonists inhibit this reflex. Repeated colorectal distention (CRD) induces Fos like immunoreactivity (Fos-LI) in the rat spinal cord. Aims-To examine the eVect of the 5-HT 3 receptor antagonist alosetron on the depressor response to CRD, and on Fos expression in the lumbosacral spinal cord. Methods-Male rats were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
82
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(86 citation statements)
references
References 39 publications
4
82
0
Order By: Relevance
“…Interestingly, several recent studies have reported an increased number of enteroendocrine cells in IBS patients (Bearcroft et al, 1998;Spiller et al, 2000;Houghton et al, 2003). Furthermore, the peripherally acting 5-HT 3 receptor antagonist alosetron blunts visceral sensation in animal models and humans and has been used clinically in the treatment of IBS (Kozlowski et al, 2000;Camilleri et al, 2001). Although circumstantial in nature, these data raise the question whether and how 5-HT affects visceral sensation and contributes to the development of visceral hypersensitivity.…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…Interestingly, several recent studies have reported an increased number of enteroendocrine cells in IBS patients (Bearcroft et al, 1998;Spiller et al, 2000;Houghton et al, 2003). Furthermore, the peripherally acting 5-HT 3 receptor antagonist alosetron blunts visceral sensation in animal models and humans and has been used clinically in the treatment of IBS (Kozlowski et al, 2000;Camilleri et al, 2001). Although circumstantial in nature, these data raise the question whether and how 5-HT affects visceral sensation and contributes to the development of visceral hypersensitivity.…”
Section: Introductionmentioning
confidence: 74%
“…Spinal 5-HT receptors also play important roles in descending modulation of pain, including visceral pain (Urban and Gebhart, 1999), and drugs that cross the blood brain barrier may exert both peripheral and central effects. The peripherally acting 5-HT 3 receptor antagonist alosetron blunts responses to colorectal distension in experimental animals and improves discomfort and pain in a subgroup of patients with functional bowel disorders (Camilleri et al, 1999;Kozlowski et al, 2000). Interestingly, other 5-HT 3 receptor antagonists do not consistently affect visceral pain in experimental animals or humans (Langlois et al, 1996;Kim and Camilleri, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…This refl ex depressor response can be used as a measure of visceral nociception. Alosetron has been shown to inhibit this vasodepressor response to colorectal distension by blocking the 5HT3 receptors (Kozlowski et al 2000). In functional brain imaging studies, alosetron has been shown to decrease brain activity in bilateral frontotemporal cortex and various limbic structures in response to colorectal distension .…”
Section: Alosetronmentioning
confidence: 99%
“…This excitatory action on intestinal sensory nerves is mediated by the 5-HT3 receptor subtype and is blocked by selective 5-HT3 receptor antagonists (e.g. alosetron) [75] . Intramural terminals of both spinal and vagal sensory nerves express 5-HT3 receptors.…”
Section: Serotonin and Functional Disordersmentioning
confidence: 99%
“…alosetron) [74,75] . Intramural terminals of both spinal and vagal sensory nerves express 5-HT3 receptors.…”
Section: Serotonin Receptors On Sensory Afferentsmentioning
confidence: 99%